The Influence of Experiential Marketing and Influencer Marketing on Purchase Decision of Skintific Skincare Products (Study on Students of UPN “Veteran” East Java at Envio Store Surabaya) - Anggun Fatmawati; Sumainah Fauziah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to examine and analyze the influence of Experiential Marketing and Influencer Marketing on the purchasing decisions of Skintific skincare products at Envio Store Surabaya. The research employs a quantitative approach with a descriptive quantitative method. The population consists of students from UPN "Veteran" East Java who have previously purchased Skintific skincare products at Envio Store Surabaya, totaling 22,976 individuals. The sample used in this study comprised 100 respondents. Data were collected through a questionnaire distributed via Google Form. Data analysis was conducted using SPSS version 27. The results indicate that Experiential Marketing and Influencer Marketing simultaneously have a positive and significant effect on the purchasing decisions of Skintific skincare products at Envio Store Surabaya. Furthermore, the findings reveal that both variables also have a positive and significant partial effect on purchasing decisions of Skintific skincare products at Envio Store Surabaya.